Method for estimating a risk for a subject suffering from hepatocellular carcinoma and method for the prognosis of hepatocellular carcinoma - LU CHANG-YI; TSAO CHAO-YUN; CHEN SHIH-YA; YEN CHIA-JUI; LIN CHIA-JU; KAN PU-YEH; LIU YIN; PENG HUI-LING; CHANG WANI (2017)
The disclosure provides a method for estimating a risk for a subject suffering from hepatocellular carcinoma, including: (a) determining methylation levels of APC gene, COX2 gene, RASSF1A gene and micro RNA-203 gene in a sample of a subject, respectively; (b) calculating a predicted score according to the methylation levels of the APC gene, COX2 gene, RASSF1A gene and micro RNA-203 gene; and (c) estimating a risk level for the subject suffering from hepatocellular carcinoma according to the predicted score. 本发明提供种评估个体罹患肝癌之风险的方法，包括：(a)分别测定个体之样本中APC之基因、COX2之基因、RASSF1A之基因以及微小RNA-203(micro RNA-203,miR-203)之基因的甲基化程度；(b)依据该APC之基因、COX2之基因、RASSF1A之基因以及微小RNA-203之基因的甲基化程度计算出预测分数；以及(c)根据该预测分数评估该个体罹患肝癌之风险程度。